Next Generation Sequencing Claims in Precision Medicine: Questions a Formulary Committee Should Ask - Paul C Langley (University of Minnesota Libraries Publishing, 2016)
The enthusiasm with which precision medicine has been embraced over the past 15 years has obscured the fact that the evidence base for biomarker-driven assessments, in particular for next generation sequencing (NGS), is limited. This applies both to the comparative performance of the various assessment tools as well as to the impact of biomarker driven decisions at the patient level. Where a genetic test is being evaluated there are five key questions a formulary committee should ask when assessing whether or not to recommend coverage and reimbursement for the test in target patient populations: (i) has the test met required standards for analytic and clinical validity? (ii) has the test been evaluated against competing tests for analytic and clinical validity? (iii) have the test-based claims met standards for credibility, evaluation and replication? (iv) has the test been accepted as part of the standard of care for patient management in the target disease state? (v) has the introduction of the test improved outcomes, including survivorship, adverse events, quality of life and costs, in the targeted population? The purpose of this commentary is twofold: first, to consider the appropriate evidentiary standards for the evaluation of a test and comparator tests; and, second, to identify questions that a formulary committee should address in submissions made for a test in health care systems. A critical issue is not only comparative claims for the test against the standard of care and comparator tests, but the assessment of test performance for the identified treatment pathways where mutations or variants are linked to recommendations for therapy options. Unless these issues are addressed it is unlikely that the promise of personalized medicine will be realized. The absence of an evidence base will deter both physicians and their patients from adopting NGS based recommendations.   Type: Commentary